Electrodynamics and the response of the geomedium to the effect of external electromagnetic fields - V.N. Shuman (Геофизический журнал, 2013)
Peculiarities of electrodynamic description of geo-medium - an open dissipative dynamic system with numerous self-organized structures have been considered. Attention is focused on the problems related to influence of external electromagnetic fields on material media, determination of density values of dissipated energy, balance equations for energy and impulse, electrodynamics of non-thermal processes in media. Specific consideration is based on K-form (Kazimir form) of Maxwell equations, which possibly gives the simplest and sequential description of general pattern of medium and field interaction. Role and importance of fractal models, which qualitatively change approaches and methods of electrodynamic description of geomedium are accentuated. It is mentioned on the base of the concept of dynamically unstable geomedium, proposed by I. L. Gufeld that under the Earth's crust conditions both thermal fluctuations and non-thermal parameters, which influence its voluminous-stressed state and produced by external electromagnetic state, may compete with the processes of interaction of light gases (hydrogen, helium) with its solid phase modulated by this interaction. It is important that in this case electromagnetic effect can be not energetically strong but correctly organized topologically, concordant with current state of geomedium, in particular, with noise levels in it. Problems of electrodynamics of dielectric media, which susceptibility in frequency range is described by fractional power dependence, important from geophysical applications viewpoint, have been considered.